Properties of Purified Staphylococcal β-Hemolysin - Gow, John A. (1969)
Purification of β-hemolysin was achieved by ammonium sulfate precipitation, Sephadex G-100 gel filtration, carboxymethyl cellulose column chromatography, and density gradient electrophoresis. Active fractions eluted from carboxymethyl cellulose contained at least one nonhemolytic protein, and omission of this step was not detrimental to the purification process. Density gradient electrophoresis yielded approximately 1.6 mg of highly active purified β-hemolysin per liter of culture supernatant liquid. Purified β-hemolysin gave a single line on gel double diffusion and immunoelectrophoresis. A single symmetrical peak formed in the analytical ultracentrifuge, and the sedimentation coefficient was calculated to be 1.7S. The purified β-hemolysin was stable at 4 C and could be lyophilized. Magnesium cations were required for full expression of β-hemolytic activity. β-Hemolysin was lethal for rabbits when injected intravenously in amounts between 40 and 160 μg. Crude β-hemolysin was more stable than purified β-hemolysin when heated at 60 C for 30 min. Purified β-hemolysin lost almost all of its activity on subsequent heating at 100 C for 10 min.